Documentation of Vascular Plants of Mudumalai Tiger Reserve, Western Ghats, India - Jansirani, P.; Raja, P.; Tagore, Johny Kumar (Indian Forester, 2021)
The wide range of climatic factors and their interaction reflect the diversity of the vegetation communities. The major vegetation types of Mudumalai Tiger Reserve (MTR) includes Southern Tropical dry thorn forest, Southern Tropical dry deciduous forest, Southern Tropical moist deciduous forest, Southern Tropical semi-evergreen, moist bamboo brakes and Riparian fringing forest. A total of 426 plant species under 311 genera belong to 100 families, including infraspecific taxa were recorded from the study area. Fabaceae is the dominant family with represents 42 species; similarly Ficus is the dominant genera with 9 species have been recorded. The MTR is a home for many rare and threatened plants. The present study we recorded 81 plants are under threatened condition. Using vegetation data collected from the larger Nilgiri Biosphere Reserve, in and around the five tribal settlements in Mudumalai Tiger Reserve. The current study concluded that the MTR poses a severe and persistent conservation threat to both within and outside protected reserve forests.